An assessment of groundwater contaminant source and evolution from underground coal gasification at the Majuba Pilot Plant - Mokhahlane, Lehlohonolo (University of the Free State, 2019)
This study undertook to investigate the geochemistry of the potential sources of inorganic groundwater contamination from a spent UCG chamber. The Eskom Majuba UCG pilot plant in South Africa was the main study area for this research. Two core drills that intercepted the spent geo-reactor retrieved residue products (ash, char and heat affected host rocks). Geochemical and mineralogical characterization of UCG residue products was done to establish the inorganic groundwater contamination risk. QEMSCAN and XRD results indicated that most of the primary mineral phases were transformed into high temperature phases. Above average levels of high temperature minerals: mullite, cordierite, tridymite and cristobalite were detected in the roof of the spent UCG chamber. Pyrite transformed into pyrrhotite as recorded by the inverse relationship in the profiles of these sulphide minerals. In general, the results established that char and rocks in the vicinity of the gasification chamber contained relatively lower pyrite levels when compared with the original lithology. Total sulphur analysis of the char recorded comparatively lower sulphur levels as compared to natural coal and this rendered the spent geo-reactor more environmentally sustainable, as lower total sulphur equates to less risk of acid rock drainage. Most of the sulphur is converted to H2S during the gasification process and transported with the syngas to the surface, where it can be removed and captured as elemental sulphur. The second objective of the study dealt with the water-rock interaction in the spent geo-reactor. The assessment of the water-rock geochemistry was conducted through leaching tests under different geochemical environments. This task was achieved by subjecting different sections of the geo-reactor to leaching by the following mediums: deionized water, hydrogen peroxide and sulphuric acid. Elements showed a pH-dependent solubility as seen by the general negative correlation factor for each element. The water elution tests (no pH buffer), released the lowest concentrations of ionic species into solution and had an alkaline final pH in most cases. The water elution results were in the main, one or several orders of magnitude lower than the other elution tests results. The peroxide leaching results recorded lower pH levels as compared to the water elution results and consequently the solubility of elements increased. Peroxide elution induces full solution oxidation and this is the basis for acid rock drainage associated with coal mining. The decrease in pH is attributed to oxidation of sulphide minerals which acidify the solution thereby increasing the solubility of elements. Acid leaching was used to assess the leaching dynamics in the spent UCG geo-reactor if acidic conditions developed. Chemical dissociation of carbonates and silicates phases failed to buffer or counter the acidity by consuming the hydronium that is responsible for the low pH. It is therefore recommended that a drop in pH below 4 in mine water around a spent UCG geo-reactor must be countered by acid neutralization strategies such as lime injection to avoid development of acid mine drainage. The mine water elution was utilized to assess the leaching dynamics under field conditions as waterrock interactions were subjected to experimental temperature of 25 and 70 °C, respectively. The following elements showed general decrease in concentration with increase in temperature Mn, Fe, Ni, Sr, Ca, M and V. The following elements however showed general increase in concentration with increase in temperature: B, K, Cu, and SO4. The distribution coefficient was used to assess dissociation of elements between the mine water and the solid surfaces of the UCG residue products. Contaminant migration was confirmed with the heat affected roof releasing the most metals into solution at 25 °C while the highest concentrations of metals mobilized into solution at 70 °C emanated from both the roof and char samples. Aluminium and Fe were the main non-mobile elements across all sections of the geo-reactor and their relative mobility was not affected by change in experimental temperature. The semi mobile metals were Ba, Ni, Cu, Mn, V while metals with great affinity to leach into water phase were Sr, V, Co, Mn, Cu, B and Pb. The higher elution ability of Pb from char samples at higher temperatures is an environmental concern as generally this element was not mobilized from other sections of the geo-reactor from both deionized water and mine water eluates, which indicates that temperature plays a role in dissolving this element from the organic surfaces. Acid base accounting was used as a predictive tool to assess the acid producing capacity of the spent geo-reactor. The NNP (net neutralising potential) was calculated in terms of the difference between acid producing (AP) and neutralising potential (NP). The analysis utilized both the acid base accounting (ABA) and net acid generation (NAG) methods of acid generation prediction. Utilizing both NNP and NAG test for potential acid generation of samples provides a more reliable evaluation technique than either test used alone. NNP characterized around 13% of samples as acid generating with only 7.5% as non-acid generating. NAG classified 26 samples (49%) as high acid generating while only 13 (24.5%) was characterized as non-acid generating. In general, acid generation is a possibility in a spent georeactors however, UCG operations are usually at very deep locations (>200 mbgl) and there might not be sources of oxygen at this depths, for the oxidation of sulphide minerals. However, oxygenated water can be introduced into the chamber during quenching or through drainage of shallow aquifers via hydraulic connections with the spent geo-reactor. The risk to groundwater contamination from UCG activities was assessed in terms of the sourcepathway-receptor model. The spent geo-reactor was identified as the source, as it houses the residue material that contain toxic species as determined by the mineralogical assessment and leaching tests. The pathway was divided into two; (1) a borehole intercepting the spent geo-reactor which provided a vertical pathway from the coal seam aquifer to the overlying aquifers. (2) the in-seam groundwater pathway (lateral extent) that was assessed by monthly groundwater data from the coal seam aquifer taken from monitoring boreholes and compared with background. Stable isotope and hydrochemistry results show that the shallow aquifer and the deep aquifer are not hydraulically connected and therefore it is unlikely that groundwater from the gasification zone would contaminate the shallow aquifer. The deep aquifer had a distinctive isotopic signature for stable isotopes from the shallower aquifers which confirms that there was no groundwater mixing in these aquifers. There was stratification in all the boreholes (monitoring and verification) assessed in terms of EC and temperature. The stratification in EC showed that the quality of water that is sitting on top of the well is better than that in the bottom. This trend suggest that in the event of fractures forming due to roof collapse or any other event that could possibly create a flow path between the cavity water and the shallower strata, the water quality will not be uniform throughout the hydraulic connection. Better water quality will preferentially be at the shallow levels with low quality water concentrated at the bottom. Time series data displayed the chemical evolution of the coal seam aquifer. The results showed no evidence of inorganic contamination from UCG activities. In most cases, the water from the verification boreholes was of lower salinity than background and monitoring boreholes. This is due to surface water that was injected into the UCG cavity during quenching. The groundwater chemistry in the geo-reactor showed a general trend of degenerating to background levels.
Thesis (Ph.D. (Geohydrology))--University of the Free State, 2019
Keywords: Underground coal gasification; Geo-reactor; Pyrometamorphism; Sanidinite facies; Acid base accounting; Mine water leaching; Stratification